The Impact of Facebook Features and Activities on Purchase Intention in the Post-COVID Development Strategy 2030 - Melvin Lee, Jing Wei; Asmaul Husna, Haris Fadzilah (2023)
Facebook is currently the most popular social media in the world. Now, Facebook not only provide certain features and activities that allowed its users to communicate with other people, but it also creates an online business platform for its users to conduct business online. However, due to the COVID19 outbreaks, the influence of Facebook features on consumers’ purchase intentions became unpredictable. In this research, the data were collected using quantitative methods and a cross-sectional research design was used. The targeted respondents for this research are undergraduates of the University of Malaysia, Sarawak, and a total of 370 responses were collected through Google Forms. The objective of this research is to identify the impact of Facebook features, such as Facebook Advertisement, Number of Likes, Sharing, and Friend Recommendations on consumer’s purchase intention. The Uses and Gratifications Theory (UGT) and Social Influence Theory (SIT) were used as the theoretical foundations for this research. IBM (SPSS) Statistics 27.0 was used to analyze the data collected from the questionnaire. This research will help marketers and businesses to utilise the use of Facebook features to generate more profit. It also serves as a guideline for consumers to better evaluate the product content on Facebook.